THE ROLE OF MEDICAL-SURGICAL NURSES IN PREVENTING HOSPITAL READMISSIONS AMONG HEART FAILURE PATIENTS: A LITERATURE REVIEW - Azza Anwar Aly , Hanaa Ibrahim El Sayed , Mervat Ali Khamis , Nadia Hassan Ali ,Awad , Hamda Ahmed Mohamed Eldesoky, Hoda Mohamed Flife, Hadaiea Ismail Abo baker, Wafaa Hassan Awad (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Background: Heart failure (HF) remains a leading cause of hospital readmissions globally, posing significant healthcare costs and patient burden. Evidence highlights the pivotal role of medical-surgical nurses in post-discharge education, care coordination, and early intervention, which significantly reduces readmissions. Aim: This critical review aims to examine the role of medical-surgical nurses in preventing hospital readmissions among heart failure patients. Data Search, Review, and Collection: Data were collected from 2018 to 2025 using databases like PubMed, CINAHL, and the Saudi Digital Library. Keywords included "heart failure," "hospital readmissions," "nursing interventions," and "patient education." Implications for Clinical Practice: This review emphasizes the need for structured nursing interventions, patient-centered education, and transitional care programs to minimize HF readmissions. Nurses are integral to achieving sustainable improvements in heart failure outcomes through education, early identification of deterioration, medication reconciliation, and emotional support. Heart failure remains a global epidemic affecting millions. By empowering patients through education and continuity of care, medical-surgical nurses can significantly mitigate the cycle of readmissions, improving both quality of life and system efficiency.